The Effect of Colloid Therapy (Gelatin) in Maintaining Hemodynamic Stability in Patients at Risk of Intraoperative Hypovolemic Shock in the Central Surgical Installation (IBS): Case Study - Krismayanti; Tahir, Takdir (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Aims: This case study investigated the effects of colloid therapy (gelatin) on maintaining hemodynamic stability in patients at risk of intraoperative hypovolemic shock during total hysterectomy and bilateral salpingo-oophorectomy.  Methods: A descriptive case study with a single case design was conducted on patient Mrs. S during the intraoperative phase, observing hemodynamics before and after colloid therapy (gelatin) administration. Results: During the intraoperative phase, in the first 40 min, there was a decrease in blood pressure to 92/52 mmHg, an increased heart rate of 117 beats/minutes, and an MAP of 65. Subsequently, blood pressure improved during the administration of colloid fluid therapy, with the patient's blood pressure reaching 113/72 mmHg, heart rate 84 beats per minute, and MAP 85 after 40 minutes. After 60 minutes of colloid fluid therapy, blood pressure was 110/62 mmHg, heart rate was 73 beats per minute, and MAP was 77.  Conclusion: Collaborative intervention with colloid therapy effectively restored and maintained the hemodynamic stability of patients at risk of hypovolemic shock during the intraoperative phase.